D6.7 - Webinars - Hadjimitsis, Diofantos G.; Evagorou, Evagoras G.; Mettas, Christodoulos; Agapiou, Athos; Lysandrou, Vasiliki; Christofe, Andreas; Tzouvaras, Marios; Papoutsa, Christiana; Nisantzi, Argyro; Themistocleous, Kyriacos; Lasaponara, Rosa; Masini, Nicola; et al. (My University, 2018)
The purpose of this Report is to describe the webinars that took place during the project, related to TASK 6. Particularly, through the webinars, all the methods and techniques used during the project are described. This deliverable includes the agenda, the participants and the presentations of ATHENA’s webinars.
Keywords: Webinars; ATHENA project